Investigation of In Vitro Cytotoxicity of Hypericum Perforatum in Pancreatic Cancer - Saç, Can; Özel, Derya, Şeyma; Yurt, Fatma (My University, 2025)
Pancreatic cancer remains one of the most aggressive malignancies with poor prognosis and limited treatment options. In view of the constraints imposed by current treatment modalities, there has been an increased focus on natural products as potential complementary agents in cancer therapy. Hypericum perforatum (HP), commonly known as St. John’s Wort, has demonstrated cytotoxic and apoptotic properties in various cancer models; however, its effects on pancreatic cancer cells are not well-studied. This study aimed to investigate the in vitro cytotoxic effects of Hypericum perforatum extract on AR42J pancreatic cancer cells. AR42J cells were cultured and treated with increasing concentrations (3.125–100 µg/mL) of HP extract for 24 and 48 hours. Cell viability was assessed using the MTT assay. Nuclear morphological changes were evaluated by DAPI staining and visualized with a Juli™ Smart Fluorescent Cell Analyzer. HP extract exhibited a dose- and time-dependent cytotoxic effect on AR42J cells. IC?? values were determined to be 12.5 µg/mL at 24 hours and 6.25 µg/mL at 48 hours. DAPI staining confirmed nuclear condensation and fragmentation in treated cells, supporting apoptosis as a mechanism of action. These results indicate that H. perforatum extract effectively reduced pancreatic cancer cell viability while inducing apoptotic cell death. These findings suggest that H.perforatum extract exerts significant antiproliferative and pro-apoptotic effects on AR42J pancreatic cancer cells. The study highlights its potential as a plant- based complementary therapeutic candidate for pancreatic cancer treatment.
Keywords: MTT assay; Pancreatic cancer; in vitro study; Hypericum Perforatum; AR42J cell; DAPI staining